Pertanggung Jawaban Pelaku Pidana Penipuan Online - Ali, Muhammad Fadlan; Imran, Suwitno Y.; Swarianata, Vifi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Abstract The purpose of this research is 1) To determine and analyze the accountability for criminals of online fraud and criminal of conventional fraud which set in the Code of Criminal Law 2) To determine and analyze the juridical consequences of Article 28 paragraph (1 ) of the Code of Information and Electronic Transactions Article 378 of the Code of Penal, as well as providing insight into the crime of online fraud that uses the internet as the main medium. The result of study is the Article 378 of the Code of Criminal Law concerning criminal fraud can not be used to punish the online fraud criminals, there are obstacles in the way to punish the criminal sanctions on criminals such as limitation of the proof which limited by the Code of Criminal Procedure (Criminal Code) and jurisdiction. Given the shortcomings in the Criminal Code, Article 28 paragraph (1) juncto Article 45 paragraph (2) of Law No. 8 of 2011 on information and electronic transactions can be used to charge the criminals to take account for his actions in the case of criminal fraud online, because Article 28 paragraph (1) of the Act ITE is Lex Specialis of Article 378 which is Lex Generalis. Juridical consequences of using Article 28 paragraph (1) Code of Information and Electronic Transactions against Article 378 of the Code of Criminal Law on online fraud is both of article in a two code laws that override and exclude each other.